Lived religion and mystical experiences : Finding an inclusive umbrella concept for varieties of experiences deemed religious - Johansson, Katarina (Approaching Religion, 2022)
This article discusses and argues for a ‘new’ and inclusive umbrella concept for varieties of experiences that have been called, inter alia, religious, spiritual, existential, paranormal, extraordinary or inexplicable. The umbrella concept to be explored is seen as a means of capturing one kind of ‘lived religion’ in contemporary society and simultaneously expanding the field of the sociology of religion. The discussion is theoretical and anchored in contemporary theories and traditions in sociology of religion, but it is also of pragmatical, methodological, empirical, and ethical concern. The main concepts that are currently in use and considered as offering a possible umbrella term for this cluster of often overlapping experiences, which are difficult to clearly define and distinguish, are summarized, and the main concepts, such as religious, spiritual and paranormal experiences, are elaborated in more detail. Thereafter follows a definition and in-depth discussion of the suggested concept of mystical experiences. In conclusion, I argue that William James’s concept of mystical experiences, with an upgraded and inclusive understanding considering religious, cultural and societal change, has the potential to work on etic, interdisciplinary and emic levels, without offending the experiencers or violating their interpretations and the meaning-making of their experiences.